THE EFFECT OF EASE OF USE, PERCEPTION OF USEFULNESS AND ELECTRONIC TRUST ON SATISFACTION OF USING QRIS AS A DIGITAL PAYMENT METHOD (CASE STUDY OF COFFEESHOP CONSUMERS IN PEKANBARU CITY) - Anasfi, Khoirul; Afwa, Awliya (Jurnal Apresiasi Ekonomi, 2025)
This study aims to determine how much influence ease of use, perceived benefits and electronic trust have on satisfaction with the use of QRIS as a digital payment method in coffee shops. This study consists of three independent variables, namely ease of use, perceived benefits and electronic trust and one dependent variable, namely satisfaction with use. The analysis method used is multiple regression analysis. The data collection method in this study is by using a questionnaire filled out by respondents, namely consumers who use QRIS as a digital payment method in coffee shops in Pekanbaru City. The results of the study obtained based on the partial test (t test) obtained: a) tthere is a significant influenceease of use towards user satisfaction, b)there is a significant influenceperception of benefitstowards user satisfaction, c)there is a significant influenceelectronic trust regarding satisfaction of use, based on simultaneous testing obtained:d)there is a significant simultaneous influence betweenease of use, perceived usefulness and electronic trusttowards user satisfaction. Keywords: Ease of Use, Perceived Benefits, Electronic Trust, Use Satisfaction